Synthesis, molecular docking, and antiepileptic activity of novel phthalimide derivatives bearing amino acid conjugated anilines - Azar Asadollahi; Mehdi Asadi; Faezeh Sadat Hosseini; Zeinab Ekhtiari; Mahmood Biglar; Massoud Amanlou (Wolters Kluwer Medknow Publications, 2019)
A series of N-aryl-2-(1,3-dioxoisoindolin-2-yl)-3-phenylpropanamides derivatives were synthesized in two steps. Phthalic anhydride and phenylalanine are first reacted under microwave radiation to form 2-(1,3-dioxoisoindolin-2-yl)-3-phenylpropanoic acid, which finally took part in an amidation reaction with different anilines. The final products were characterized by infrared, proton nuclear magnetic resonance (1H NMR) and mass spectroscopy techniques. The antiepileptic activity of the synthesized compounds at a fixed dose of 10 mg/kg was evaluated by pentylenetetrazole at 70 mg/kg induced seizure threshold method in male mice (n = 5) and compared with aqueous DMSO (10 %, v/v; as negative control) and thalidomide (70 mg/kg; as positive control). The results indicated that compounds 5c, 5e, and 5f as well as thalidomide significantly have higher latency time than what observed with aqueous DMSO (P < 0.05). The seizure latency threshold for 5e and 5f were statistically similar to the results of thalidomide but compound 5c showed significantly higher latency time than thalidomide. While, the electron-deficient benzene ring (5a and 5b) has demonstrated the lowest activity but compound 5e, which is the most electron rich product among tested compounds, showed good antiepileptic activity. Molecular docking was performed in order to understand how the synthetized compounds, interact with gamma-aminobutyric acid (GABA)A receptor. Docking results were in good harmony with experimental data and indicated that lowest binding energy belongs to compound 5c, which has strongest interactions with the active site of GABAA receptor. Compound 5c could be used for further investigation.